(untitled) (Research, Society and Development, 2020)
The study aimed to analyze scientific productions about the complications that smoking has on pregnancy, investigate the problems developed during pregnancy due to tobacco use and verify what preventive measures are being taken to decrease tobacco use during pregnancy. An integrative literature review study, using the PICo strategy, was attributed to P: pregnant women, I: complications and Co: nicotine in electronic databases. There were 11 articles published between 2015-2020. The first category addressed the incidence of pregnant women who smoke. The second category identified the complications of pregnant smoking mothers. The third is the Complications presented by the RN. The present study allows health professionals to understand more about the side effects that smoking has on pregnancy and the developmental problems presented by fetuses who have had contact with smoking and the impact that smoking prevention policies have on women pregnant women.